(untitled) (Journal of Interdisciplinary Insights, 2024)
This study explores the transformation of teaching concepts in College English education and the strategies for cultivating ICC. It highlights the limitations of traditional teaching methods, which often focus on language knowledge while neglecting cultural aspects. The study proposes a student-centered, culturally immersive approach that integrates language learning with cultural experiences. By incorporating diverse cultural materials, innovative teaching methods, and modern educational technologies, educators can foster students’ cultural sensitivity, global vision, and adaptability. The study also addresses current challenges in teaching ICC, such as imbalanced cultural content in textbooks, the separation of language and cultural teaching, and the underutilization of technology. It further emphasizes the importance of comprehensive evaluation systems that assess students’ ICC alongside language skills. Teachers are identified as key facilitators in this process, with a need for continuous professional development to enhance their ability to teach intercultural competence effectively. The findings offer valuable insights for reforming College English teaching and preparing students to navigate the complexities of global communication. Future research can focus on interdisciplinary approaches, the use of big data, and AI in teaching to further enhance ICC cultivation.